Potassium Efficiency of Wheat and Sugar Beet Evaluated Under Field Conditions - El Dessougi, Hanadi I. (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to investigate the potassium (K) efficiency of wheat and sugar beet under field conditions and to identify the varying mechanisms or factors behind their efficiency. Data were obtained from a long term fertilizer experiment, on a K "fixing" sandy clay loam in Bavaria, southern Germany, in which K fertilization rates varied from 0 to 1000 kg K ha-1 year-1 with the last K application in 1986. In 2003, sugar beet and spring wheat were sown on March 13 th and April 4 th , respectively. At 4 and 5 harvests for wheat and sugar beet, respectively, random samples of shoots, roots and soil of each species from the unfertilized (-K) and the highest fertilizer level of 1000 kg K ha-1 (+K) treatments were analyzed. Sugar beet and wheat had similar K efficiency producing 76 % and 80 % beet and grain yield on unfertilized compared with fertilized treatments, respectively. As compared to wheat, sugar beet had a higher internal K requirement, two times higher shoot growth rate (GRs), 34% to 48 % of the wheat root length (RL), and consequently a larger GR/RL, that is higher demand for K uptake on the roots. However, sugar beet showed an exceptionally high uptake efficiency of the single roots or influx, which was 5 times higher in unfertilized treatments, as compared with wheat. Wheat K efficiency was attributed to a higher utilization efficiency or lower internal requirement, slow growing shoots and a large root system. Further investigations are necessary to study the mechanism by which sugar beet was able to achieve a higher influx than wheat.